Regulating the Witness and Victim Protection Agency: Managing Safe Houses for Victims in Indonesia - Herawati, Ratna; Hanum, Willy Naresta; Nurjanah, Neni (LITIGASI, 2025)
The state is obliged to protect victims of sexual violence, especially those who are most vulnerable, and this obligation is also a fundamental right of victims. One of these rights is access to temporary housing, often called a safe house, provided by LPSK. However, the governance of safe house management in the regions is not optimal, especially in the relationship between institutions at the center and regions and the representation of institutions in the regions, so it is not optimal in guaranteeing victims' rights. The urgency of this study is to analyze the LPSK policy in managing safe houses throughout Indonesia, the various challenges of institutional relations, and the distribution of representative safe houses in the regions. This study uses doctrinal research with analytical-descriptive specifications and utilizes secondary data. The legislative approach is used to examine laws and regulations on protecting victims of violence and developing LPSK institutions. The conceptual approach analyzes the concept and theory of state institutions, authority, and victim protection. This study shows that legal protection for victims of sexual violence to fulfill the right to a safe house by LPSK does not yet have integrated cooperation with the regional office managing the safe house. Cooperation is actually carried out with other institutions. The implementation of LPSK protection for victims of sexual violence has experienced institutional problems that have affected the formation of LPSK representatives at the regional level and coordination between regional institutions, which is exacerbated by the lack of quantity and quality of human resources...